2022
DOI: 10.1002/1878-0261.13273
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer disease recurrence after radical prostatectomy is associated with HLA type and local cytomegalovirus immunity

Abstract: Prostate cancer is a heterogeneous disease with a need for new prognostic biomarkers. Human leukocyte antigen (HLA) genes are highly polymorphic genes central to antigen presentation to T‐cells. Two alleles, HLA‐A*02:01 and HLA‐A*24:02, have been associated with prognosis in patients diagnosed with de novo metastatic prostate cancer. We leveraged the next‐generation sequenced cohorts CPC‐GENE and TCGA‐PRAD to examine HLA alleles, antiviral T‐cell receptors and prostate cancer disease recurrence after prostatec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…We also found a positive association between a high CMV IgG VirScore in prostate tissue 14,30 , reflecting presence and diversity of CMV IgG antibodies, with CMV-pp71 epithelial abundance (n=15, p=0.003) (Figure 1B), further supporting an association between CMV immunity and epithelial CMV infection. Prostates of CMV seropositive donors did not have higher prevalence of inflammatory infiltrates with lymphocytes than in CMV seronegative donors (Figure S1A).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…We also found a positive association between a high CMV IgG VirScore in prostate tissue 14,30 , reflecting presence and diversity of CMV IgG antibodies, with CMV-pp71 epithelial abundance (n=15, p=0.003) (Figure 1B), further supporting an association between CMV immunity and epithelial CMV infection. Prostates of CMV seropositive donors did not have higher prevalence of inflammatory infiltrates with lymphocytes than in CMV seronegative donors (Figure S1A).…”
Section: Resultssupporting
confidence: 58%
“…Ethical permission for study of human samples was granted by the regional ethics committee of Sweden (2010/313-31/3). Prostate tissue and blood samples were collected from post-mortem donors between 2015 and 2020 through KI Donatum, Karolinska Institutet, Stockholm, Sweden, as described in 14 and 9 ; post-mortem cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between HCMV presence in tumors and survival was first observed in patients with glioblastoma [ 61 ]. Several studies then indicated that HCMV is associated with higher malignancy grade and poor outcome not only in patients with glioblastoma and but also in patients with breast, colon, ovarian and prostate cancer [ 62 , 63 , 64 , 65 , 66 ]. If the virus plays a role as a tumor promoting agent for various cancer forms, viral protein expression should be considered and evaluated as a prognostic marker, and this could open for new therapeutic possibilities for patients.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that individuals harboring these particular genetic polymorphisms are at an elevated risk of experiencing post-surgical advancement of their prostate malignancy. Consequently, distinct immunogenetic profiles may serve as prognostic markers, offering a nuanced understanding of disease trajectory in prostate cancer [29][30][31]. In the present study, we applied NGS Illumina technology to genotype two HLA class I loci (HLA-A and HLA-B) in patients with PCa and healthy controls (HCs).…”
Section: Introductionmentioning
confidence: 99%